طريقة المباشرة لترقية المهارة الكلام - Wafa, Ali; Dimyati, Afifuddin; Mufid, Zain; Islamiya, Meilina Nur; Zuhdiyah, Khofifatu (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study discusses the mubasyaroh method in learning Arabic. The researcher uses the mubasyaroh method as the object of research with the aim of knowing how to use the method in increasing students' maharah al-kalam. The research method used by the researcher in this study is a qualitative method, namely a method that emphasizes more on the quality side of the entity. The mubasyaroh method can improve students' speaking ability in learning Arabic, therefore we teach the mubasyaroh method to improve students' speaking skills in learning Arabic.